Development of Pratylenchus coffeae in Biochar Applied Soil, Coffee Roots and Its Effect on Plant Growth - Dwi Suci Rahayu; Niken Puspita Sari (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2017)
Biochar improve physical, chemical and biological properties of soil. It may also be used as botanical pesticides. The experiment was aimed to determine the effect of biochar on population development of parasitic nematode Pratylenchus coffeae. The experiment was carried out in Nematology Laboratory and in a greenhouse of Indonesian Coffee and Cocoa Research Institute (ICCRI), Jember, Indonesia. The experiment was arranged according to completely randomized design with six treatments of biochar concentrations, i.e. 4%; 3%; 2%; 1%; 0.5% and 0% dry weight of soil. Research results revealed that biochar application of 4.0% was effectively killed 74.5% of P. coffeae, while the lowest mortality level of 37.5% at biochar 0.5% treatment. In the greenhouse trial, application of biochar 4.0% was the most effective in suppressing the population of parasitic nematode in coffee seedlings. Application of biochar was also able to increase the growth and biomass of coffee seedlings.